Mild nitric acid treatments to improve multiwalled carbon nanotubes dispersity and solubility in dielectrophoresis mediums - Abdulhameed, Abdullah; Mohtar, Mohd Nazim; Hamidon, Mohd Nizar; Abdul Halin, Izhal (Taylor & Francis, 2021)
The major limitation of carbon nanotubes (CNTs) is their poor solubility in the common solvents. Solving the solubility issue of CNTs is comprehended either by functionalizing the CNTs or using a dispersity agent. Agents such as ionic surfactant dramatically alter the suspension conductivity causing undesirable thermal flow in dielectrophoresis (DEP) mediums. In this study, the lack of CNTs solubility in common solvents was resolved by functionalizing multi-wall carbon nanotubes (MWCNTs) using a mild regulated procedure. The mild treatment was used to maintain the electrical conductivity of MWCNTs, since its essential for their dielectrophoretic response. Fourier-transform infrared (FTIR) spectroscopy, high-resolution transmission electron microscopy (HRTEM), and Raman spectroscopy were used to investigate the treatment quality. The ability of different solvents to dissolve MWCNT agglomerates after treatment was analyzed using ultraviolet-visible (UV-Vis) spectroscopy and dynamic light scattering (DLS) analysis. The characterization results indicate that the treated MWCNTs by the presented procedure contain hydroxylic and carboxylic functional groups and showed strong solubility in water, dimethylformamide (DMF) and acetone. This study provides a better solution to improve the processability of MWCNTs in common solvents without degrading their electrical conductivity.